Towards performance assessment of fuel cell integration into buildings - Sofia Boulmrharj; Mohammed Khaidar; Mustapha Siniti; Mohamed Bakhouya; Khalid Zine-dine (Energy Reports, 2020)
The integration of Combined Heat and Power (CHP) systems, especially fuel cell systems, into buildings have attracted a lot of interest these last years. It is due to their higher efficiency, cleanliness and their capability for producing both valuable thermal energy and electricity, from a single source of fuel, such as natural gas or hydrogen. Their high efficiency, which can reach 85%-90%, leads to a decrease in both greenhouse gas emissions and costs when compared to the conventional methods of generating heat and electricity separately. The aim of this work is towards efficient integration of a Proton Exchange Membrane (PEM) fuel cell into buildings in order to supply it with both electricity and heat. Experiments on a system composed of fuel cell, converter, and hydrogen tank have been carried out and compared to the simulations conducted using Matlab/Simulink where the system's model has been developed. Simulation and experimental results are compared in order to show the accuracy of the models that have been developed and the efficiency of the fuel cell when operating as a CHP system to supply the building with both electricity and heat.
Keywords: 330; CHP system; Fuel cell; Hydrogen; Matlab/Simulink softwares